Effects of bone marrow mesenchymal stem cells (BM-MSCs) on rat pial microvascular remodeling after transient middle cerebral artery occlusion - Lapi, Dominga; Vagnani, Sabrina; Sapio, Daniela; Mastantuono, Teresa; Boscia, Francesca; Pignataro, Giuseppe; Penna, Claudia; Pagliaro, Pasquale; Colantuoni, Antonio (Frontiers in Cellular Neuroscience, 2015)
Previous studies have shown that the pial microcirculation remodeling improves neurological outcome after middle cerebral artery occlusion (MCAO), accompanied by higher expression of vascular endothelial growth factor (VEGF) and endothelial nitric oxide synthase (eNOS), modulating in vivo angiogenesis. This study was aimed to assess the effects of bone marrow mesenchymal stem cells (BM-MSCs) infused after MCAO on rat pial microcirculation. Animals were subjected to 2 hour MCAO followed by BM-MSCs infusion into internal carotid artery. Pial microcirculation was observed at different reperfusion times by fluorescence microscopy. Geometric characteristics of arteriolar networks, permeability increase, leukocyte adhesion, perfused capillary density, VEGF and endothelial nitric oxide synthase (e-NOS) expression were evaluated. Green fluorescent protein (GFP)-BM-MSCs were used to evaluate their distribution and cell phenotype development during reperfusion. BM-MSCs stimulated a geometric rearrangement of pial networks with formation of new anastomotic vessels sprouting from preexistent arterioles in the penumbra at 7-14- 28 days of reperfusion. At the same time VEGF and eNOS expression increased. GFP-BM-MSCs appear to be involved in endothelial and smooth muscle cell programming in the infarcted area. In conclusion, transient MCAO induced pial vascular remodeling characterized by arteriolar anastomotic arcades (originated from pre-existent arterioles in penumbra area) able to overlap the ischemic core supplying blood to the neuronal tissue. BM-MSCs appear to accelerate angiogenic processes facilitating new vessel formation; this mechanism was promoted by an increase in VEGF and eNOS expression.